2019
DOI: 10.1016/j.agrformet.2019.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of near-surface wind speed variability on wind erosion in the eastern agro-pastoral transitional zone of Northern China, 1982–2016

Abstract: Wind erosion in arid and semi-arid areas is an important global environmental issue, and changes in wind speed trends over time play a key role in wind erosion dynamics. In a warming climate, scientists have recently observed a widespread decline in wind speed, termed "stilling". Here, we apply the Revised Wind Erosion Equation Model (RWEQ) to simulate the variability of wind erosion and quantify the impact of wind speed changes on soil degradation dynamics over the eastern agro-pastoral transitional zone of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 71 publications
2
42
0
Order By: Relevance
“…In addition to precipitation, SWS was the second crucial climatic factor influencing vegetation variation, since the wind speed was negatively correlated with soil moisture content, soil texture, and nutrient content [58][59][60]. A similar result indicated that the SWS has shown a downward trend in recent decades [61]. Therefore, the decreased SWS in recent decades had a positive effect on vegetation growth from a soil moisture perspective.…”
Section: The Ndvi Response To Climate Changementioning
confidence: 86%
“…In addition to precipitation, SWS was the second crucial climatic factor influencing vegetation variation, since the wind speed was negatively correlated with soil moisture content, soil texture, and nutrient content [58][59][60]. A similar result indicated that the SWS has shown a downward trend in recent decades [61]. Therefore, the decreased SWS in recent decades had a positive effect on vegetation growth from a soil moisture perspective.…”
Section: The Ndvi Response To Climate Changementioning
confidence: 86%
“…S2) since the early 1990s (Y. . As successfully applied previously (e.g., Azorin-Molina et al 2016;Shi et al 2019), the R package Climatol (Guijarro 2017; http://www.climatol.eu/; last accessed 1 November 2019) was used to perform quality control, relative homogenization, and missing data infilling on raw DMWS series. Climatol works with ''normalized'' values, and here normalizations were achieved by using the normal ratio method (dividing observed DMWS by the long-term averages of the DMWS series).…”
Section: B Quality Control and Homogenizationmentioning
confidence: 99%
“…where V g refers to geostrophic wind (m s 21 ), f is the Coriolis parameter (s 21 ), H is the geopotential height (m 2 s 22 ), and qH is the pressure difference associated with the distance qd (m). Further, vertical transport of atmospheric momentum changes was represented as vertical wind shear between 1000 and 850 hPa (Shi et al 2019) and atmospheric thermal stratification instability (index A, dimensionless; Zhang et al 2014). Vertical wind shear [Eq.…”
Section: Atmospheric Circulation Modes and Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the observations at 822 surface weather stations, Vautard et al (2010) showed that the surface wind speed has been reduced by 5%-15% over almost all continents in the Northern Hemisphere (NH) midlatitudes over . A recent study also showed a decrease in surface wind speeds and wind power potential in most of NH over the past four decades (Tian et al 2019) exerting adverse impacts on windgenerated electricity (Sherman et al 2017) and the dispersion of air pollutants (Li et al 2019b), reducing evaporation (McVicar et al 2012), and affecting soil erosion (Zhang et al 2019). However, the mechanisms related to the observed wind stilling are not well understood (Wu et al 2018, Zeng et al 2018.…”
Section: Introductionmentioning
confidence: 99%